Predição de propagação de fissuras através de modelos constitutivos locais e técnica de construção progressiva da trajetória de descontinuidade - Manzoli, Osvaldo Luís [UNESP] (Univ Politecnica Catalunya, 2011)
This paper addresses the study of the quality and objectivity of responses obtained with the distinct formulations (symmetric and non-symmetric) of the discontinuity embedded finite elements, as well as with the local continuum approach (smeared model), in which the softening law dependent on the element size is combined with a scheme to track the discontinuity path. The study is based on the concepts of kinematic and static consistency of the embedded discontinuity formulations. (C) 2010 CIMNE (UPC). Published by Elsevier Espana, S.L. All rights reserved.
Prediction of crack propagation via local constitutive models with a scheme to track the discontinuity path
Keywords: Strain localization; Embedded crack elements; Smeared crack model; Crack path; Mesh dependence